Impact of the calculation algorithm on biexponential fitting of diffusion-weighted MRI in upper abdominal organs - Barbieri, Sebastiano; Donati, Olivio F.; Froehlich, Johannes M.; Thoeny, Harriet C. (Magnetic resonance in medicine, 2016)
Purpose To compare the variability, precision, and accuracy of six different algorithms (Levenberg–Marquardt, Trust‐Region, Fixed‐Dp, Segmented‐Unconstrained, Segmented‐Constrained, and Bayesian‐Probability) for computing intravoxel‐incoherent‐motion‐related parameters in upper abdominal organs. Methods Following the acquisition of abdominal diffusion‐weighted magnetic resonance images of 10 healthy men, six distinct algorithms were employed to compute intravoxel‐incoherent‐motion‐related parameters in the left and right liver lobe, pancreas, spleen, renal cortex, and renal medulla. Algorithms were evaluated regarding inter‐reader and intersubject variability. Comparability of results was assessed by analyses of variance. The algorithms' precision and accuracy were investigated on simulated data. Results A Bayesian‐Probability based approach was associated with very low inter‐reader variability (average Intraclass Correlation Coefficients: 96.5–99.6%), the lowest inter‐subject variability (Coefficients of Variation [CV] for the pure diffusion coefficient Dt: 3.8% in the renal medulla, 6.6% in the renal cortex, 10.4–12.1% in the left and right liver lobe, 15.3% in the spleen, 15.8% in the pancreas; for the perfusion fraction Fp: 15.5% on average; for the pseudodiffusion coefficient Dp: 25.8% on average), and the highest precision and accuracy. Results differed significantly (P < 0.05) across algorithms in all anatomical regions. Conclusion The Bayesian‐Probability algorithm should be preferred when computing intravoxel‐incoherent‐motion‐related parameters in upper abdominal organs. Magn Reson Med 75:2175–2184, 2016. © 2015 Wiley Periodicals, Inc.